Preparation and characterization of graphene oxide quantum dots/silver nanoparticles and investigation of their antibacterial effects - Oktay, Busra; Erarslan, Azime; Ustundag, Cem Bulent; Ozerol, Esma Ahlatcioglu (IOP Publishing Ltd, 2024)
Water, constituting 75% of Earth and vital for sustaining life, faces global contamination challenges, causing approximately 2 million annual deaths from waterborne diseases, as reported by the World Health Organization. Technological strides in water purification leverage antibacterial materials to combat this issue. At the forefront is silver nanoparticles (AgNP), renowned for antimicrobial efficacy. Their action involves damaging bacterial cells and hindering metabolism, causing structural and physiological alterations in microbial membranes. Graphene oxide (GO) emerges as a potent biocide, and when combined with AgNP, it enhances antibacterial activity. The resulting composite, known as antibacterial graphene oxide quantum dots (GOQD), exhibits photocatalytic behavior when exposed to sunlight or UV rays, generating reactive oxygen species (ROS). This synergistic composite, particularly the GOQD/AgNP combination, proves effective in eliminating bacteria and fungi from water. In a recent study, GOQD was synthesized, and the GOQD/AgNP combination was prepared. Structural analyses, utilizing techniques such as FTIR, Zeta sizer, and TEM, revealed heightened antibacterial activity with increasing AgNP ratios. The GOQD/AgNP samples formed inhibition zones of 11.75 mm, 10 mm, and 9.88 mm against pathogenic bacteria Escherichia coli (E. coli), Salmonella typhi (S. typhi), and Staphylococcus aureus (S. aureus), respectively. Notably, the GOQD/AgNP composite demonstrated a synergistic antibacterial effect, showcasing its potential for widespread applications. This material holds promise for deployment in drinking water treatment plants and water storage tanks, ensuring water safety for consumption. Beyond water purification, the composite's antibacterial properties hint at significant potential in medical and industrial realms, marking a crucial step toward safeguarding water sources and enhancing global public health.
Keywords: antibacterial; graphene oxide quantum dot; nanomaterial; silver nanoparticles; SILVER NANOPARTICLE; DOTS; Materials Science